Insegurança alimentar em tempos de pandemia do COVID-19 no Brasil: revisão de literatura - PINHEIRO, Andressa da Silva (2023)
The new Coronavirus was first identified in Wuhan, China in 2019 and brought several challenges to the global health system, as it soon spread to other continents and was declared by the World Health Organization as a “Pandemic” on January 31. 2020. In Brazil, the first case identified was in the municipality of São Paulo in February 2020, which led states and municipalities to take measures to delay the collapse. However, these measures, despite being efficient, had negative effects on the economy. Therefore, the concern about the Food and Nutritional Security of Brazilian households arises. Therefore, the objective of this research is to identify the factors that influence the increase in the prevalence of Food and Nutritional Insecurity that may be associated with the worsening of this impasse during the Covid-19 Pandemic to Food Security in Brazil. It is an integrative review with a qualitative approach, in which it uses the literature as a basis to study and analyze the points related to the topic addressed. The final sample consists of 12 references that were considered relevant for this study. After reading in full, the following points were discussed: Global Crisis, Food and Nutritional Insecurity in Brazil, Socioeconomic and Demographic Aspects, Food, Covid-19, Housing Conditions, Mental Health and Public Policies Against the Pandemic. It is concluded that Food and Nutrition Insecurity is not a recent fact in Brazil and the aspects that influence the increase in levels are repeated, but with the Pandemic this reality was intensified reaching more serious levels, and it is necessary that these aspects are evaluated for the taking measures to alleviate this situation.